SOCIAL JUSTICE AND COVID 19 IN THE 'NEW SOUTH AFRICA: INVOKING RAMOSEAN MEDITATIONS IN PANDEMIC TIMES (The Pretoria Student Law Review, 2021)
In this contributory essay to the 2021 Special Section of the PSLR spotlighting ‘Social Justice and COVID-19’, I attempt to challenge portrayals of the novel coronavirus (COVID-19) as an ‘indiscriminate’ and ‘equal opportunity’ assailant. In doing so, I endeavour to bring to the fore a reading of social injustices experienced during the ongoing COVID-19 pandemic that implicates not only systemic disadvantages inherited from apartheid but also the legacies of unjust colonial conquest. By underscoring memory as the possibility condition for restorative social justice within a progressively unjust South Africa, I draw on philosopher Mogobe Ramose’s counter-discourse meditations problematising the pervasiveness of colonial-apartheid conquest in a post-1994 liberal democratic polity. Accordingly, I align myself with perspectives that consider substantive social justice in a stratified ‘new’ South Africa to be a decolonial justice carved out by an African experience and memory, with the restoration of unjustly dispossessed land as a possibility condition for social cohesion.
Keywords: decolonial justice; social cohesiveness; social justice; Ramosean meditations